Subtle interaction between Ag and O 2 : a near ambient pressure UV photoelectron spectroscopy (NAP-UPS) investigations - Ghosalya, Manoj Kumar (Journal of Chemical Sciences, 2018)
The Ag-O2 interaction, which is at the center-stage of Ag-catalyzed partial oxidation reactions, is studied with NAP-UPS up to 0.2 mbar O2 pressure between 295 and 550 K. Three temperature regimes were identified for distinct Ag-O2 interaction, which are (a) 295–390 K, where mainly dissociative chemisorption of O2 happens, (b) 390–450 K, where diffusion of O-atoms into the sub-surfaces of Ag is prominent, and (c) >450 K, where metastable oxide forms on polycrystalline Ag surfaces. The work function (WF) of Ag changed from 4.95 (≤390 K) to 5.30 eV (390–450 K), and then to 5.7 eV (≥450 K) at 0.1 mbar O2 pressure. Oxygen population in the sub-surfaces imparts crucial modifications to Ag at 390–450 K; it makes the surface to be electron-deficient that relates to the change in the WF of Ag and facilitates the formation of space charge layer on Ag surface. Oxygen adsorbed on such modified Ag-surfaces is electrophilic in nature, and this appears at a higher binding energy in core level XPS than the chemisorbed oxygen on metallic Ag. This is supported by angle-dependent NAP-XPS studies. The subsurface population of oxygen in Ag no longer persists at >410 K when the O2 supply is removed. A high ratio of antibonding/bonding O 2p bands suggests the unique silver-oxygen interaction under the measurement conditions.
Keywords: Electronic Structure; epoxidation; heterogeneous catalysis; Surface Science